2004
DOI: 10.1111/j.1365-2141.2004.04808.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel FLT3 point mutations within exon  14 found in patients with acute myeloid leukaemia

Abstract: SummaryInternal tandem duplications in FLT3 are the most common mutation in acute myeloid leukaemia (AML), with agarose gel electrophoresis of polymerase chain reaction products (PCR/agarose) being the screening method of choice for these mutations. As PCR/agarose screening does not detect small mutations, single-stranded conformational polymorphism analyses (PCR/SSCP) were used in an attempt to identify previously unrecognized point mutations in FLT3 exons 14 and 15 of 140 AML patients, using newly designed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…16 Novel primers for Flt3 exons 14 and 15 were developed for this purpose, as previously described. 18 Cytogenetic studies were performed on G-banded preparations. 19 Fluorescent in situ hybridization (FISH) to detect the t(15;17) was performed using probes for the promyelocytic leukemia (PML) gene and the retinoic acid receptor-alpha (RARA) gene at 15q22 and 17q21, respectively (Vysis, Downers Grove, IL, USA), according to the manufacturer's instructions.…”
Section: Molecular and Cytogenetic Methodsmentioning
confidence: 99%
“…16 Novel primers for Flt3 exons 14 and 15 were developed for this purpose, as previously described. 18 Cytogenetic studies were performed on G-banded preparations. 19 Fluorescent in situ hybridization (FISH) to detect the t(15;17) was performed using probes for the promyelocytic leukemia (PML) gene and the retinoic acid receptor-alpha (RARA) gene at 15q22 and 17q21, respectively (Vysis, Downers Grove, IL, USA), according to the manufacturer's instructions.…”
Section: Molecular and Cytogenetic Methodsmentioning
confidence: 99%
“…Their prevalence seems to be lower than 1% in all AML subtypes and has not yet been established in cytogenetically normal AML (CN-AML). 19,20 Lastly, a novel gain-of-function mutation (K663Q), located not in the AL but in the N-terminal part of TKD, has been recently identified in AML. 21 Interestingly, a recent study stressed the importance of functional studies, since among the different FLT3 mutations reported outside the JMD and the TKD, some were not associated with kinase activation, and did not contribute to leukemogenesis.…”
Section: Flt3mentioning
confidence: 99%
“…Akin to FLT3-ITDs, FLT3-TKDs promote constitutive phosphorylation of the FLT3 protein, thereby leading to disruption of normal haematopoiesis. The third type of FLT3 alterations, point mutations in the juxtamembrane domain of the FLT3 gene, is relatively rare (Stirewalt et al, 2004;Reindl et al, 2006).…”
Section: Mutations Of the Fms-related Tyrosine Kinase 3 (Flt3) Genementioning
confidence: 99%